A Continuous Test Method for Dynamic Change of Real Mesostructures of Soil. (24th January 2022) - Qian, Xiaoxu; Liu, Xin; Yao, Yunlong; Pu, Shikun; Sheng, Ke; Wang, Guisen; Hong, Baoning; Feng, Dingyu
Abstract : The regularity of dynamic change of real mesostructures of soil is the foundation of the macro- and mesointegrated research. Mesoscale research about continuous image acquisition in real soils, identifying and quantifying mesostructures, is the subject of current interest. Soil mesostructure measurement method is the basis of modeling, and the development of rapid, direct, and lower-cost methods has great practical value for engineering practice. Combined with conventional triaxial loading test equipment, optical measurement, mesoscopic imaging tracking system, and digital image technology, a new method for measuring the dynamic change of the soil mesostructure is designed. This integrated approach to observation and acquisition is realized by direct observation and continuous image capture for dynamic change of real mesostructures of soil. The methods are used to analyze the high compressibility of a certain clay, shear zone development of cement soil, and erosive effects of ecological soil in order to investigate the continuous variation of mesostructures during the shear test. The aim of this paper is to provide a simple, straightforward, continuous, and low-cost test method for revealing the characteristics of consecutive change of real mesostructures of soil in the conventional triaxial test.